Electrical resistivity properties of soils - Ong, Ying Xiong (Nanyang Technological University, 2020)
Electrical resistivity of soil has become a more popular method to study soil properties over the years due to advancement in geotechnical studies on this topic. It is less time-consuming, lower cost and non-invasive compared to other existing methods such as bore hole sampling. Soil electrical resistivity survey does have its own set of challenges as data interpretation may be disturbed by other factors such as salinity. In this study, laboratory tests have been conducted to investigate the correlation between electrical resistivity and thermal conductivity of soil under the influence of salinity. Fine river sand and kaolin clay are tested for temperature changes and electrical resistivity changes at different salinity. There is a strong correlation between electrical resistivity and thermal conductivity of soil at different levels of salinity. A power function with an added parameter for salinity is used to approximate thermal conductivity from electrical resistivity of soil. The study concludes with possible improvements and recommendations to future research.